Efficacy of triple antiplatelet therapy (aspirin, clopidogrel, and cilostazol) in cerebral infarction presenting with hemiplegia: A case report and critical appraisal of current evidence - Amran, Muhammad Yunus; Yunus, Muhammad Akbar; Hidayah, M Fajrin; La’biran, Fitri Jafani; Gunadi, Siti Giranti Ardilia; Hawari, Irbab (Acta Biomedica Atenei Parmensis, 2025)
Cerebral infarction, a type of stroke, occurs when blood vessels in the brain become occluded. Triple antiplatelet therapy (aspirin, clopidogrel, and cilostazol) has been used to prevent recurrent episodes in patients with cerebral infarction; however, it carries a risk of bleeding. In this case report, we demonstrated the effectiveness of triple antiplatelet therapy in a patient with cerebral infarction and hemiplegic motor deficits. A 38-year-old man presented with paralysis of the right side of his body and slurred speech after resting for 14 hours before hospital admission. He denied prior head trauma, fever, headache, nausea, or loss of consciousness. There was no history of hypertension, diabetes mellitus, or heart disease, but the patient reported smoking 24 cigarettes daily. A head CT scan revealed an infarction in the external capsule and left corona radiata. Cerebral angiography showed occlusion of the left lenticulostriate artery, a branch of the middle cerebral artery (MCA) at the M1 segment. The patient was treated with citicoline, mecobalamin, atorvastatin, and ranitidine, in addition to triple antiplatelet therapy (aspirin, clopidogrel, and cilostazol). After eight days of treatment, the motor strength in the right upper and lower extremities showed significant improvement. The use of triple antiplatelet therapy in cerebral infarction remains a controversial topic due to the associated risk of major bleeding. However, in this case, the administration of triple antiplatelet therapy, guided by the TARDIS study, resulted in a favorable clinical outcome.